Analysis and evaluation of the impact of railway infrastructure parameters changes on “Rail Baltica” project implementation - Palevičius, Vytautas; Kaušylas, Mantas (International Conference “Environmental Engineering”, 2020)
“Rail Baltica” project is priority project No 27 “Rail Baltica” axis Warsaw-Kaunas-Riga-Tallinn-Helsinki, approved by Decision No 884/2004/EC of the European Parliament and of the Council of 29 April 2004 amending Decision No 1692/96/EC on Community guidelines for the development of the trans-European transport network (European Union, 2004). An article analyzes the changes in the main parameters of the 1435 mm gauge railway infrastructure during the whole period of the “Rail Baltica” project, determines their impact on the project implementation timeline, purposes and results, highlights basic parameters which need to be met during modernization. On this basis, the main criteria for the evaluation of Rail Baltica rail infrastructure were selected. An expert survey was conducted to evaluate the criteria. The Kendall method was used to calculate the criteria weights. The article ends with a scientific discussion.